Lower limb arterial calcification and its clinical relevance with peripheral arterial disease - Dong, Yue; Liu, Yuankang; Cheng, Panpan; Liao, Hongli; Jiang, Cuiping; Li, Ying; Liu, Shuhua; Xu, Xiangyang (Frontiers in Cardiovascular Medicine, 2023)
Lower limb arterial calcification (LLAC) is associated with an increased risk of mortality and it predicts poor outcomes after endovascular interventions in patients with peripheral artery disease (PAD). Detailed histological analysis of human lower artery specimens pinpointed the presence of LLAC in two distinct layers: the intima and the media. Intimal calcification has been assumed to be an atherosclerotic pathology and it is associated with smoking and obesity. It becomes instrumental in lumen stenosis, thereby playing a crucial role in disease progression. On the contrary, medial calcification is a separate process, systematically regulated and linked with age advancement, diabetes, and chronic kidney disease. It prominently interacts with vasodilation and arterial stiffness. Given that both types of calcifications frequently co-exist in PAD patients, it is vital to understand their respective mechanisms within the context of PAD. Calcification can be easily identifiable entity on imaging scans. Considering the highly improved abilities of novel imaging technologies in differentiating intimal and medial calcification within the lower limb arteries, this review aimed to describe the distinct histological and imaging features of the two types of LLAC. Additionally, it aims to provide in-depth insight into the risk factors, the effects on hemodynamics, and the clinical implications of LLAC, either occurring in the intimal or medial layers.